Watchers on the hill - Whitson, Stephanie Grace (Whitson, Stephanie Grace. Pine Ridge portraits, 2014)
Charlotte Valentine Bishop struggles to trust God to heal the wounds of her past when she returns to Fort Robinson, Nebraska, with her child, in search of a safe haven, and is confronted with a number of surprises, including the appearance of two former suitors.